P437 Risk of immunomediated adverse events or secondary loss of response to infliximab in elderly patients with inflammatory bowel disease: a cohort study of the ENEIDA registry. (25th January 2019) - Calafat, M; Mañosa, M; Panes, J; Nos, P; Iglesias, E; Vera, I; López-Sanromán, A; Guardiola, J; Taxonera, C; Mínguez, M; Martín, M D; de Castro, L; et al.
Abstract: Background: Infliximab is one of the most used biological drugs in inflammatory bowel disease (IBD). Immunomediated adverse events (IAE) are of the most frequent reported infliximab-related adverse events. Elderly patients have differential pharmacodynamic and pharmacokinetic characteristics. We recently reported an increased risk of thiopurine-related AEs in this population; hence, it would be relevant to ascertain if combined treatment is adequate in this population. Our aim was to evaluate the rate of infliximab-related IAE in elderly IBD patients. Methods: All adult patients in the ENEIDA registry (a large, prospectively maintained database of the Spanish Working Group in IBD–GETECCU) who received a first course of infliximab treatment were identified. Patients were selected in two cohorts regarding the age at the beginning of infliximab treatment: over 60 years, and between 18 and 50 years of age. The rates of IAE recorded in the ENEIDA database (infusion reactions, delayed hypersensitivity, oedema, allergy, anaphylaxis, psoriasis, lupus-like syndrome) were compared, as well as the rate of secondary loss of response (SLR). Results: We included 939 (12%) patients who started infliximab over 60 years and 6844 (88%) patients below 50 years. The rate of IAE (15% vs. 15%, ns) and treatment withdrawal due to IAE (13% vs. 12%, ns) was similar in both groups. Neither differences were observed according to IAE: infusion reactions (8.3% vs. 8.2%), late hypersensitivity (1.4% vs. 1.2%), paradoxical psoriasis (0.9% vs. 1.4%) and drug-induced lupus erythematosus (0.7% vs. 0.6%). Patients below 50 years were significantly more often treated with concomitant immunosuppressants (57% vs. 48.1% >60 years, p < 0.05). In the multi-variate analysis, combination with immunosuppressants (OR 0.741; 95% CI 0.64–8.5, p < 0.05) and female sex (OR 1.8; 95% CI 1.6–2.1, p < 0.05) were the only independent predictors to develop IAE. The rate of SLR was also similar in both study groups (20% vs. 21%). Combination therapy with immunosuppressants was the unique risk factor to develop SLR (OR 0.85; CI 95% 0.73 to 0.98, p = 0.021). Conclusions: Elderly IBD patients who start treatment with infliximab have a similar risk of developing IAE and SLR than younger patients. From this point of view, elderly would benefit from combination therapy.